2014
DOI: 10.1111/jace.12853
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Aluminum Oxynitride (γ‐AlON) Transparent Ceramics with Modified Gelcasting

Abstract: Transparent aluminum oxynitride (AlON) ceramics have been prepared through aqueous gelcasting forming technique starting from the raw materials of single phase AlON powders. The powder was specially treated for anti‐hydrolysis in ethanol before the shaping technique. The surface‐treated AlON powders could then be dispersed in an aqueous‐organic solution to prepare stable slurries containing 35 vol% solids loading. The obtained stable slurries were subsequently casted, calcined, and pressureless sintered at 195… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…Recently, Yang et al reported a gelling system using a water‐soluble copolymer of isobutylene and maleic anhydride (commercially named Isobam, Molecular Weight: 55 000‐65 000) working as not only dispersant but also gelling agent. This new gelling system has been used for fabricating many kinds of high‐performance ceramics including translucent Al 2 O 3 , transparent YAG and AlON, porous Al 2 O 3 and Si 3 N 4 due to its advantages of nontoxicity, low addition and spontaneous gelling at room temperature in air. However, it is not suitable to disperse nanoscaled MgAl 2 O 4 powder with Isobam owing to its long molecular chain which will make the slurry with low solid loading and high viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Yang et al reported a gelling system using a water‐soluble copolymer of isobutylene and maleic anhydride (commercially named Isobam, Molecular Weight: 55 000‐65 000) working as not only dispersant but also gelling agent. This new gelling system has been used for fabricating many kinds of high‐performance ceramics including translucent Al 2 O 3 , transparent YAG and AlON, porous Al 2 O 3 and Si 3 N 4 due to its advantages of nontoxicity, low addition and spontaneous gelling at room temperature in air. However, it is not suitable to disperse nanoscaled MgAl 2 O 4 powder with Isobam owing to its long molecular chain which will make the slurry with low solid loading and high viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al have proposed an alternative gelling mechanism whereby the relatively long chains of ISOBAM (55‐65 kDa rather than 3‐15 kDa of most traditional dispersants) bridge adjacent ceramic particles by adsorbing partially onto the surface of one particle and partially onto the surface of another rather than adjacent ISOBAM chains interacting with each other as previously proposed . This proposed mechanism, while thermodynamically unlikely, is not directly refuted based on the presented data.…”
Section: Resultsmentioning
confidence: 69%
“…30 During aqueous gelcasting, one of the most important effects on the strength of green body is the gel network generated by the in-situ polymerization of organic monomers. 18 In contrast, MAM-MBAM has much lower toxicity than AM-MBAM, 32 and the green body possesses sufficient strength (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) to permit machining. [16][17][18][19] In these systems, since the main component of AM-MBAM is a neurotoxin, the application of the acrylamide system is limited.…”
Section: Introductionmentioning
confidence: 99%